Evolution of broad-line emission from active galactic nuclei. Issue 4 (28th January 2014) - Elitzur, Moshe; Ho, Luis C.; Trump, Jonathan R.
Abstract: Apart from viewing-dependent obscuration, intrinsic broad-line emission from active galactic nuclei (AGN) follows an evolutionary sequence: type 1 → 1.2/1.5 → 1.8/1.9 → 2 as the accretion rate on to the central black hole is decreasing. This spectral evolution is controlled, at least in part, by the parameter L bol / M 2/3, where L bol is the AGN bolometric luminosity and M is the black hole mass. Both this dependence and the double-peaked profiles that emerge along the sequence arise naturally in the disc-wind scenario for the AGN broad-line region.